The initial powder-refinement-induced donor-like effect and nonlinear change of thermoelectric performance for Bi2Te3-based polycrystalline bulks. (8th June 2017) - Hu, Jie; Fan, Xi'an; Zhang, Chengcheng; Jiang, Chengpeng; Feng, Bo; Xiang, Qiusheng; Li, Guangqiang; He, Zhu; Li, Yawei
Abstract: p-type Bi0.5 Sb1.5 Te3 bulks were prepared from different original sizes of 36–203 μ m by the resistance pressing sintering (RPS) method. It was demonstrated that the original powder refinement introduces lattice defects and facilitates a donor-like effect, resulting in a decrease of the carrier concentration and an increase of the effective mass of the carrier. The finer the original powder is, the higher the electrical resistivity and Seebeck coefficient are, and the lower the thermal conductivity is. Although the sintered sample from the smallest sized powders possessed the minimum thermal conductivity, its figure of merit was unsatisfactory due to the low electrical transport performance, and the sintered sample from the 200 ∼ 300 meshed original powders obtained a maximum figure-of-merit of 0.95 at 340 K. In addition, it was observed that the phenomenon of nonlinear change in electrical transport performance with initial powder refinement was due to the percolation effect. In short, the present work confirms that the initial powder size has a great influence on the thermoelectric properties of Bi2 Te3 -based materials, which should be taken seriously in our follow-up work.